Integrasi Pijat Laktasi dan Edukasi Gizi untuk Peningkatan Produksi ASI Eksklusif: Studi Mixed Method pada Ibu Menyusui di Kabupaten Rokan Hulu - Andria; Romy Wahyuny; Devi Novita Sari; Bia Arrafah Syifa; Rindi Atikha; Budi Yanto (Jurnal Ilmu Kebidanan, 2025)
Exclusive breastfeeding coverage in Rokan Hulu Regency remains stagnant at 56%, far below the national target of 80%. This low achievement is influenced by insufficient maternal nutrition knowledge, postpartum stress, and limited social support. This study aims to analyze the effectiveness of lactation massage and nutrition education interventions in improving breast milk production and maternal knowledge. The research employed a mixed-method explanatory sequential design with a quasi-experimental pre-test and post-test control group, followed by in-depth interviews. A total of 60 breastfeeding mothers with infants aged 0–6 months were selected through purposive sampling. Quantitative data were analyzed using paired t-test and independent t-test, while qualitative data were examined thematically. The results showed a significant increase in breast milk volume (≥20%) and maternal nutrition knowledge scores (≥25 points) in the intervention group compared to the control group (p < 0.05). Qualitative findings revealed that the intervention enhanced mothers’ confidence, reduced stress, and strengthened community support. This study concludes that combining lactation massage and nutrition education is effective in improving exclusive breastfeeding practices and should be integrated into primary healthcare services